Introgression of heat shock protein genes for development of heat tolerant chilli (Capsicum annuum L.) genotypes through marker-assisted backcrossing - Magaji, Usman (2018)
Domestic production of chilli is insufficient (52% self-sufficiency level) and can hardly meet 70% of local demand due to some factors including the poor performance of local varieties under high temperatures above 42 ºC. The optimum growing temperature for chilli ranged from 20 to 30 ºC. Climate change especially high temperature is projected to negatively impact future agricultural production worldwide. According to reports, Malaysia will lose about 10% of major staples food by 2030 due to climate change, which is projected to rise average temperature by 0.3 ºC to 4.5 ºC and this warmer climate will cause a rise in sea level, and this will reduce crop yield. Development of improved heat-tolerant chilli varieties will contribute to self-sufficiency in chilli in Malaysia. Backcrossing together with simple sequence repeat marker strategy was adopted to improve popular Malaysian Kulai 907 (Capsicum annuum L.) for heat tolerance. The use of molecular markers in backcross breeding and selection contributes significantly to overcome the main drawbacks such as increase linkage drag and time consumption, in the conventional breeding approach and to speed up the genome recovery of the recurrent parent. The approach was adopted to introgress heat shock protein gene(s) from AVPP0702, a heat-tolerant variety, into the genetic profile of Kulai 907, a high-yielding chilli but heat sensitive. Introgression of heat shock proteins (Hsps) genes has shown considerable success in improvement of crop plants such as maize and rice against heat stress. However, no study has been reported on the introgression of Hsps genes in chilli for the improvement of chilli heat tolerance. The main objective of this study was to develop heat tolerant variety of chilli with high yielding potential and while the specific objectives were; to introgress Hsp genes from heat tolerant (AVPP0702) to high yielding Kulai 907 variety, to identify polymorphic molecular markers for heat tolerant characteristics and recipient parent genome recoveries (RPG) and to validate the backcross progenies for heat tolerance (Hsp loci). Local Kulai 907 variety was used as the recurrent parent and AVPP0702 was used as the donor parent. The parents were grown on seed trays and parental screening was carried out with 252 simple sequence repeat markers (SSR). DNA of young fresh leaves was extracted using CTAB method. Out of the 252 SSR markers, 27% showed clear polymorphism between heat sensitive and tolerant parent. Sixty-eight markers appeared to be polymorphic and used to estimate the recovery of the recurrent parent in the backcross generations; BC1F1, BC2F1, BC3F1 and BC3F2. The average RPG of the selected four BC1F1 plants was 80.75% which were used to produce the BC2F1 generation. BC1-P7 plant was the best in BC1F1 generation having the highest recovery 83.40% and positive to Hsp-linked markers (Hsp70-u2 and AGi42). After three successive generations of backcrossing, the average genome recovery (RPG) of the recurrent parent in the selected plants in BC3F1 population was 95.37% and BC3F2 population was 97.90%. Hsp gene expression analysis was carried out on BC1F1, BC2F1, BC3F1 and BC3F2 selected genotypes with high recovery of the recurrent parent. The Hsp genes are found to be up-regulated with more than 10.9-, 18.4-, 8.8- and 22.2- fold increase when exposed to heat treatment. The pattern of Hsp expression in the backcross generations was similar with the donor parent (up-regulated). This confirms the successful introgression of stress responsive gene (Hsp) into Kulai 907 variety. Twelve improved heat-tolerant chilli genotypes, namely; BC1-P7-P10-P1-P2, BC1-P7-P10- P1-P9, BC1-P7-P10-P1-P11, BC1-P7-P10-P3-P5, BC1-P7-P10-P1-P13, BC1-P7-P10-P3-P4, BC1- P7-P10-P4-P7, BC1-P7-P10-P4-P9, BC1-P7-P10-P4-P14, BC1-P7-P10-P3-P16, BC1-P7-P10-P4- P15, BC1-P7-P10-P4-P18 were selected from the BC3F2 population that had homozygous Hsp alleles from AVPP0702 and recurrent genome recovery of Kulai 907 (average RPG 97.9%). Most of the morphological and agronomical traits were recovered in the selected improved-heat tolerant genotypes from Kulai 907 such as plant height (75.94 cm), number of days to 50% flowering (56.5%), number of fruits (91.6), stem length (22.3 cm), stem diameter (6 cm), fruit length (13.3 cm) and weight (17.5 cm) and total fruit yield per plant (862.3 g).